P155 Fluticasone furoate (FF)/Vilanterol (VI) once daily reduces rescue medication use both day and night. (12th November 2015) - Jacques, LA; Forth, R; Yates, L; Leather, DA
Abstract : Introduction and objectives: FF/VI is the first once daily inhaled corticosteroid/long-acting b2 -agonist combination available for the treatment of asthma. Data from five phase III studies that have previously been presented have generally demonstrated a sustained 24 h improvement in lung function and improvement in rescue-free 24 h periods compared with placebo (P), FF alone or fluticasone propionate (FP). Due to differences in study comparators, duration of study and primary endpoints, integration of the study results has not been possible therefore each study is considered separately. Methods: Post-hoc analyses of diary card data from the 5 studies were performed to examine whether there was any difference in the contribution of the day and night time rescue medication use to the 24 h rescue-free period. Patients recorded in an electronic diary card the number of inhalations of rescue salbutamol/albuterol inhalation aerosol used during the day and night. To be counted as rescue-free during the day or night the patient needed to record a no use of rescue medication during that period. Results: The post-hoc analyses demonstrated that the improvements in day and night time rescue –free periods were similar to the 24 h rescue free periods. See Figure 1 below. Conclusions: In general the benefit of FF/VI on rescue free 24 h periods is reflected in the improvements seen in day and night time rescue use.